Neuropeptides in sensory signal processing - Carr, Richard; Frings, Stephan (Cell & tissue research, 2019)
Peptides released from trigeminal fibers fulfill well-understood functions in neuroinflammatory processes and in the modulation of nociceptive signal processing. In particular, calcitonin gene-related peptide (CGRP) and substance P (SP), released from afferent nerve terminals, exert paracrine effects on the surrounding tissue and this has been recently highlighted by the prominent parcrine role of CGRP in the development of headache and migraine. Some recent communications suggest that these sensory neuropeptides may also modulate the workings of sensory organs and influence afferent signals from nose, tongue, eyes and ears. Here, we briefly review the evidence for modulatory effects of CGRP and SP in the sensory periphery.
Published online: 30 October 2018
Gesehen am 01.04.2019